THE EFFECTS OF POLITICAL INSTITUTION ON SOURCES OF ECONOMIC GROWTH: CASE OF DEVELOPING COUNTRIES - Irwanda Wisnu Wardhana (Widyariset, 2011)
This research attempts to determine if political institutions has significant influences on sources of economic growth in developing countries. The research employs panel data of 65 developing countries by following the methodology of Pinto and Timmons. The results show that more democratic regime decreases investment rates; and increases foreign direct investment to GDP ratio. However, political institutions in developing countries bring insignificant effects to secondary enrollment rate, labor supply and trade to GDP ratio. This research enriches the empirical findings on interaction between political institutions and economic performance especially for the caseof developing countries.